2016
DOI: 10.18632/oncotarget.14355
|View full text |Cite
|
Sign up to set email alerts
|

Circulating miR-1 as a potential biomarker of doxorubicin-induced cardiotoxicity in breast cancer patients

Abstract: Cardiotoxicity is associated with the chronic use of doxorubicin leading to cardiomyopathy and heart failure. Identification of cardiotoxicity-specific miRNA biomarkers could provide clinicians with a valuable prognostic tool. The aim of the study was to evaluate circulating levels of miRNAs in breast cancer patients receiving doxorubicin treatment and to correlate with cardiac function. This is an ancillary study from “Carvedilol Effect on Chemotherapy-induced Cardiotoxicity” (CECCY trial), which included 56 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
91
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(94 citation statements)
references
References 37 publications
3
91
0
Order By: Relevance
“…For example, plasma miR-1 is associated with the doxorubicin-induced cardiotoxicity in BC patients. Thus, this miRNA, which influences cardiac functions, may provide clinicians with a valuable prognostic tool for avoiding cardiomyopathy and heart failure in BC patients [33]. Moreover, a genome-wide expression assay identified a signature of 4 serum miRNAs (miR-18b, miR-103, miR-107 and miR-652) that predicted tumor relapse and reduced overall survival in triple-negative BC patients [34].…”
Section: Mirnas As Prognostic Tumor Markers For Bcmentioning
confidence: 99%
“…For example, plasma miR-1 is associated with the doxorubicin-induced cardiotoxicity in BC patients. Thus, this miRNA, which influences cardiac functions, may provide clinicians with a valuable prognostic tool for avoiding cardiomyopathy and heart failure in BC patients [33]. Moreover, a genome-wide expression assay identified a signature of 4 serum miRNAs (miR-18b, miR-103, miR-107 and miR-652) that predicted tumor relapse and reduced overall survival in triple-negative BC patients [34].…”
Section: Mirnas As Prognostic Tumor Markers For Bcmentioning
confidence: 99%
“…Circulating miR-1 was found up-regulated in DOX-treated rats and in breast cancer patients treated with DOX [137,138].…”
Section: Mir-1mentioning
confidence: 95%
“…miR-1 levels were associated with changes in LVEF, and its levels were useful to discriminate patients affected by cardiotoxicity from unaffected subjects better than cTnI levels [138].…”
Section: Mir-1mentioning
confidence: 97%
“…↑miR-1 in blood plasma of rats after doxorubicin treatment [105] ↑miR-1 in blood plasma of cancer patients after doxorubicin treatment [106] ↓miR-1 in blood plasma of rats after doxorubicin-induced injury [107] ↑miR-1 in heart tissue of rats after doxorubicin treatment [108] ↓miR-1 in blood plasma of cancer child and young adult patients after anthracycline treatment [109] ↓miR-1 in blood plasma of breast cancer patients after doxorubicin treatment [110] miR-21 ↑miR-21 in mice hearts after doxorubicin treatment [108,111,112] Abbreviations…”
Section: Type Of Cvd Mir Findings Referencementioning
confidence: 99%
“…Several studies also focused on the investigation of the role of miRs in doxorubicin-induced cardiotoxicity in cancer patients. Rigaud et al [106] evaluated circulating levels of miRs in breast cancer patients receiving doxorubicin treatment. They found that circulating levels of miR-1, as well as cTnI, increased during the treatment while overall left ventricular ejection fraction (LVEF) tended to decrease over 12 months.…”
Section: Role Of Mir-1 and Mir-21 In The Heart Injury Caused By Anthrmentioning
confidence: 99%